1999
DOI: 10.1161/01.str.30.9.1887
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the COL5A1 Coding Sequence Are Not Common in Patients With Spontaneous Cervical Artery Dissections

Abstract: Background and Purpose-The dermal connective tissue of most patients with spontaneous cervical artery dissections (sCAD) contains abnormal collagen fibers. This suggests a predisposing connective tissue defect. The ultrastructural abnormalities in the skin of patients with sCAD have similarity with the morphological alterations in patients with Ehlers-Danlos syndrome type II, a dominant hereditary disorder that has been correlated in some patients to mutations within the genes encoding type V collagen. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 25 publications
0
25
0
3
Order By: Relevance
“…However, these studies have been markedly underpowered, mainly due to the low prevalence of CAD, which made it difficult to reach sufficient sample sizes; none *cDNA from cultured dermal fibroblasts. †These studies reported synonymous polymorphisms and genetic variants that were also found in healthy control subjects, considered as not being disease-causing mutations; 2 studies used single-stranded conformational polymorphism analysis (SSCP) to detect mutations 53,55 ; all other studies used direct sequencing.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, these studies have been markedly underpowered, mainly due to the low prevalence of CAD, which made it difficult to reach sufficient sample sizes; none *cDNA from cultured dermal fibroblasts. †These studies reported synonymous polymorphisms and genetic variants that were also found in healthy control subjects, considered as not being disease-causing mutations; 2 studies used single-stranded conformational polymorphism analysis (SSCP) to detect mutations 53,55 ; all other studies used direct sequencing.…”
Section: Future Directionsmentioning
confidence: 99%
“…[32][33][34]39,47,48 None of the identified mutations, however, was suggested to play a major role in the cause of CAD.…”
Section: Gene Mutation/sequencing Studiesmentioning
confidence: 99%
“…2 Thus far, the tested candidate genes for mutations in ECM molecules, for example, collagen V, have been negative. 5 An alternative pathophysiological mechanism could be vessel wall alteration by MMPs. Recently, naturally occurring sequence variations have been detected in the promotor region of MMP genes.…”
Section: Discussionmentioning
confidence: 99%
“…5 For restriction fragment length polymorphism analysis, the 435-bp polymerase chain reaction product containing the C-1562T SNP was digested with NspI restriction enzyme and run on a 2% agarose gel stained with ethidium bromide (Figure 1). Sequencing was performed in only a few individuals to confirm the nature of each band seen on the gels.…”
Section: Methodsmentioning
confidence: 99%